Lewis's medical-surgical nursing : assessment and management of clinical problems - Harding, Mariann; Kwong, Jeffrey; Roberts, Dottie; Hagler, Debra; Reinisch, Courtney (St. Louis, Missouri : Elsevier, Inc, 2020)
""Lewis's Medical-Surgical Nursing, 11th Edition" gives you a solid foundation in medical-surgical nursing. This thoroughly revised text includes a more conversational writing style, an increased focus on nursing concepts and clinical trends, strong evidence-based content, and an essential pathophysiology review. Content covers all aspects of nursing care including health promotion, acute intervention, and ambulatory care. Helpful boxes and tables make it easy for you to find essential information, and a building-block approach makes even the most complex concepts simple to grasp. Key topics such as interprofessional care, delegation, safety, and prioritization are integrated throughout. Additionally, extensive drug therapy information and diagnostic studies tables give you a full picture of care. Best of all -- a complete collection of learning and study resources helps you learn more effectively and offers valuable, real-world preparation for clinical practice" -- From product description
Professional nursing -- Health equity and culturally competent care -- Health history and physical examination -- Patient and caregiver teaching -- Chronic illness and older adults - Stress management -- Sleep and sleep disorders -- Pain -- Palliative and end-of-life care -- Substance use disorders -- Inflammation and healing -- Genetics -- Immune responses and transplantation - Infection -- Cancer -- Fluid, electrolyte, and acid-base imbalances -- Preoperative care -- Intraoperative care -- Postoperative care -- Assessment and management: visual problems -- Assessment and management: auditory problems - Assessment: Integumentary system -- Integumentary problems -- Burns - Assessment: Respiratory system -- Upper respiratory problems -- Lower respiratory problems -- Obstructive pulmonary diseases - Assessment: Hematologic system -- Hematologic problems - Assessment: Cardiovascular system -- Hypertension -- Coronary artery disease and acute coronary syndrome -- Heart failure -- Dysrhythmias -- Inflammatory and structural heart disorders -- Vascular disorders - Assessment: Gastrointestinal system -- Nutritional problems -- Obesity -- Upper gastrointestinal problems -- Lower gastrointestinal problems -- Liver, biliary tract, and pancreas problems - Assessment: Urinary system -- Renal and urologic problems -- Acute kidney injury and chronic kidney disease -- Assessment of endocrine system -- Diabetes mellitus -- Endocrine problems - Assessment: Reproductive system -- Breast disorders -- Sexually transmitted infections -- Female reproductive problems -- Male reproductive problems -- Assessment of nervous system -- Acute intracranial problems -- Stroke -- Chronic neurologic problems -- Dementia and delirium -- Spinal cord and peripheral nerve problems -- Assessment of musculoskeletal system -- Musculoskeletal trauma and orthopedic surgery -- Musculoskeletal problems -- Arthritis and connective tissue diseases -- Critical care -- Shock, sepsis, and multiple organ dysfunction syndrome -- Acute respiratory failure and acute respiratory distress syndrome -- Emergency and disaster nursing -- Appendix A: Basic life support for health care professionals -- Appendix B: Nursing diagnoses -- Appendix C: Laboratory reference intervals
Revised edition previously published as: Medical-surgical nursing : Assessment and management of clinical problems / Sharon L. Lewis [and five others]. 10th edition. [2017]
Includes bibliographical references and index
Keywords: Nursing -- Textbooks; Surgical nursing -- Textbooks; Nursing Care; Nursing Assessment; Perioperative Nursing